Imitation as a tool for research and assessment of early language development: A pilot study of word and non-word repetition - Mariscal, Sonia; Gallego, Carlos (Revista de Investigación en Logopedia, 2013)
The ability to repeat words and pseudowords as a measure of phonological memory clearly correlates with lexical development and it is a good marker of serious clinical speech disorders. However, most part of research has been done with children who speak English and /or are over the age of 4 years old. This paper presents a repetition task of this type, suitable to Spanish children from 2 to 4 years of age. 18 words and 18 paired pseudowords, systematically manipulated in its prosodic structure and length, were presented to a total of 53 children. The words (monosyllabic, bisyllabic and trisyllabic) were selected based on their frequency in children’s speech and were taken from the vocabulary list of the Spanish version of the MacArthur-Bates Communicative Development Inventories. A test of receptive vocabulary was also administered. The repetition task produced high levels of response, even with younger children. The results show sensitivity of the task to the age, the type of stimulus and the items length. The performance shows a significant relationship with performance in the vocabulary test. The implications of the overall results are discussed in relation to existing theoretical approaches and to the controversial question of what these types of tasks exactly measure. The value of these tasks as an assessment method of early phono-lexical skills in Spanish it is also highlighted.